인천광역시 및 인근 지역의 건설용 골재 유통현황 분석 연구 - 백철승(Chul-Seoung Baek); 유병운(Byoung-Woon You); 김건기(Kun-Ki Kim); 장유정(Yu-Jeong Jang); 이진영(Jin-Young Lee) (자원환경지질, 2024)
A survey of concrete plants in Incheon Metropolitan City and Gyeonggi Province was used to conduct an analysis of aggregate transport distance and production forms, as well as to evaluate the features and current status of aggregates distribution. As a result, areas such as Incheon, Siheung, Bucheon, Gimpo, and Siheung, where the distance to the demand points is less than 20 km, exhibited bidirectional distribution whereas Paju, Yongin, Yangju, and Pocheon, with distances ranging from 20 to 50 km is showed a unidirectional distribution pattern supplying aggregates exclusively to Incheon. Survey on manufacturing forms, more than 85% of the gravel dispersed in the Incheon area is made up of crushed aggregates derived from rocks discharged at construction sites indicating a considerable skew in supply chain. These findings are predicted to have a detrimental influence on aggregate supply in the long run, necessitating policy changes targeted at building an optimal aggregate distribution market. 인천광역시와 경기도에 소재한 레미콘 사업장을 대상으로 한 설문조사 결과를 기반으로 골재 운반거리 및 생산형태 분석을 수행하였으며, 골재 유통 특성과 현황을 해석하였다. 그 결과 수요지 도달거리가 20km 이내인 인천, 시흥, 부천, 김포, 시흥 지역은 생산과 타지역간 거래가 많은 양방향 유통형태를 가지며 20~50km인 파주, 용인, 양주, 포천 지역은 인천으로만 골재를 공급하는 단방향 유통형태를 나타내었다. 그리고 생산형태별 유통량 조사결과 인천지역에서 유통되는 자갈의 85% 이상이 건설현장에서 배출되는 암석으로 만든 부순골재로 공급망이 많이 편중된 것으로 나타났다. 이러한 결과들은 장기적으로 골재공급에 부정적인 영향을 줄 것으로 예상되며 적절한 골재 유통시장 형성을 위한 정책적 해결방안이 필요하다.